PENGARUH PENERAPAN NILAI KARAKTER BERBASIS KEARIFAN LOKAL SIPAKATAU SIPAKAINGE SIPAKALEBBI (3S) TERHADAP SIKAP EMPATI SISWA PADA PEMBELAJARAN IPS MELALUI MODEL RATIONAL BUILDING - Asmaul Husnah Amiruddin, - (2023)
This research is motivated by the importance of students' rational thinking skills in the 21st century to prevent ethical complications, especially among students in Makassar. The purpose of this study is to determine the influence of implementing local wisdom-based character values, known as Sipakatau Sipakainge Sipakalebbi (3S), on students' empathy in Social Studies learning through the rational building model in Class VII of UPT SPF SMP Negeri 33 Makassar. The results of this study are: (1) there is a difference in students' empathy in the experimental class before and after the implementation of character values based on local wisdom Sipakatau Sipakainge Sipakalebbi (3S) through the rational building model in Social Studies learning, (2) there is a difference in students' empathy in the control class before and after the implementation of conventional learning models in Social Studies, (3) there is a significant difference in empathy between the experimental group, which is categorized as high, and the control group, which is categorized as low, and the implementation of character values based on local wisdom Sipakatau Sipakainge Sipakalebbi (3S) has a high influence on students' empathy. The conclusion of this research is that the implementation of Sipakatau Sipakainge Sipakalebbi (3S) using the rational building model encourages students to explore 15 local wisdom values from Sipakatau Sipakainge Sipakalebbi (3S), discuss social issues related to the topic "Human Activities in Meeting Needs," and make moral decisions based on the values of Sipakatau Sipakainge Sipakalebbi (3S) to enhance students' empathy capacity. The improvement in students' empathy attitudes is observed through moral discussion activities and sociodrama. Students' cognitive empathy, which involves the ability to see situations from others' perspectives and consider common interests, as well as students' affective empathy, which entails the ability to directly feel others' emotions and emotionally respond to others' feelings. Keywords: Character Education, Local Wisdom, Sipakatau Sipakainge Sipakalebbi (3S), Rational Building Model, Empathy Attitude